Optimizing Arabic Speaking Skills Through Learning Methods In Islamic Boarding Schools - Muafaq, M. Fadil; Mutniati, Vebri Putri; Nuzula, Jannatul Firdausi; Ariarta, Aliffany Pualam; Ulfaturrahmah, Ulfaturrahmah; Latif, Muhammad Sabri (Yayasan Rahmat Islamiyah, 2024)
This research aims to explore how the Arabic Language Learning Curriculum at the Al-Irsyad 07 Islamic Boarding School in Batu City, as well as the implementation of Arabic Language Learning Methods at the Al-Irsyad 07 Islamic Boarding School in Batu City uses a qualitative approach with a case study method. Data collection techniques include participant observation, in-depth interviews and documentation studies which are analyzed using the Miles and Huberman model through data processing, data presentation and verification. The research results show that learning Arabic includes writing, speaking and listening skills, which are useful for understanding and communicating religious texts in Islamic boarding schools.Effective Arabic language learning methods are very important for improving students' speaking skills. This research emphasizes the importance of optimizing Arabic speaking skills through Islamic boarding school learning methods. As well as providing practical recommendations regarding Arabic speaking skills using learning methods at Islamic boarding schools.